Convection-enhanced delivery for treatment of brain tumors. Issue 12 (December 2007) - Ferguson, Sherise D; Foster, Kimberly; Yamini, Bakhtiar
Recently, innovative therapies have been developed for the treatment of malignant gliomas. Unfortunately, adequate delivery of these therapies has been a major obstacle to clinical success. Intravenous administration is restricted by the presence of the blood––brain barrier while local delivery, such as with drug-impregnated wafers, results in limited parenchyma penetration. Convection-enhanced delivery is a promising method for the delivery of macromolecules to the CNS. Convection-enhanced delivery involves the infusion of therapeutic agents via surgically implanted catheters and uses a pressure gradient to achieve a greater volume of distribution compared with that seen with diffusion alone. This article will review the development of convection-enhanced delivery and its use in the treatment of malignant gliomas.